2022
DOI: 10.1101/2022.08.19.504524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Male harm suppresses female fitness to affect the dynamics of adaptation and evolutionary rescue

Abstract: One of the most pressing questions we face as biologists is to understand how climate change will affect the evolutionary dynamics of natural populations and how these dynamics will in turn affect population recovery. Increasing evidence shows that sexual selection favours population viability and local adaptation. However, sexual selection can also foster sexual conflict and drive the evolution of male harm to females. Male harm is extraordinarily widespread and has the potential to suppress female fitness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Experimental evolution studies comparing populations evolving under monogamy and polygamy are a testament to the fact that these two effects often simultaneously impact population viability (Chenoweth et al., 2015; Whitlock & Agrawal, 2009) and the multivariate comparison of our experimental evolution lines confirms that evolution under sexual selection in C. maculatus follow these general predictions closely (Figure 1b). Recently, theoretical studies have highlighted the additional role of sexual selection in impacting population demography via costly sociosexual interactions arising from mating competition (Flintham et al., 2023; Gómez‐Llano et al., 2023; Martínez‐Ruiz & Knell, 2017). Such demographic impact is predicted to be particularly important when it coincides with episodes of rapid environmental change that necessitate evolutionary rescue (Martínez‐Ruiz & Knell, 2017; Svensson & Connallon, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evolution studies comparing populations evolving under monogamy and polygamy are a testament to the fact that these two effects often simultaneously impact population viability (Chenoweth et al., 2015; Whitlock & Agrawal, 2009) and the multivariate comparison of our experimental evolution lines confirms that evolution under sexual selection in C. maculatus follow these general predictions closely (Figure 1b). Recently, theoretical studies have highlighted the additional role of sexual selection in impacting population demography via costly sociosexual interactions arising from mating competition (Flintham et al., 2023; Gómez‐Llano et al., 2023; Martínez‐Ruiz & Knell, 2017). Such demographic impact is predicted to be particularly important when it coincides with episodes of rapid environmental change that necessitate evolutionary rescue (Martínez‐Ruiz & Knell, 2017; Svensson & Connallon, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Known examples of such male adaptations include harmful genitalia that scar females during mating (Stutt & Siva‐Jothy, 2001), or aggressive mate guarding to reassure paternity (Blum, 2012). Recent theoretical studies have shown that this type of sexual conflict could lead to increased extinction risk in already maladapted populations (Flintham et al., 2023; Gómez‐Llano et al., 2023; Martínez‐Ruiz & Knell, 2017). Moreover, as males of high genetic quality are likely to impose more harm to their female mates compared to males of low quality (Baur et al., 2022; Londoño‐Nieto et al., 2022; Yun et al., 2017), this effect could cancel out or even outweigh any potential population benefits of purifying sexual selection on male genetic quality (Chenoweth et al., 2015; Flintham et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Harmful male adaptations to females (male harm) are incredibly pervasive, diverse and sophisticated across the tree of life 8 . On the one hand, male harassment of females during pre-copulatory competition for mating has been documented in many vertebrate and invertebrate species 14 . On the other, post-copulatory competition has given rise to male harm adaptations that are similarly widespread and far more complex, ranging from toxic ejaculates 15 to adaptations for traumatic insemination that include seminal darts 16 , spiny penises and even genital ablation 17,18 .…”
Section: Mainmentioning
confidence: 99%
“…Male harm thus drives antagonistic female-male co-evolution in a host of behavioural and morphological traits 8 , and may even act as an engine of speciation 19,20 . More importantly, male harm frequently leads to a "reproductive tragedy of the commons" where selection on male fitness impacts population demography by depressing net female productivity 14 , even to the point of facilitating extinction 21 . Recent theoretical models suggest that such negative effects may compound when harmful traits are linked to condition 22 , in which case good-genes selection can feed back to intensify male harm 23 and male harm can slow down evolutionary rescue 14 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation